Communication and coordination: Experimental evidence from farmer groups in Senegal - Aflahagah, Fo Kodjo Dzinyefa; Bernard, Tanguy; Viceisza, Angelino (International Food Policy Research Institute, 2015)
Coordination failures are at the heart of development traps. Although communication can reduce such failures, to date experimental evidence has primarily been lab based. This paper studies the impact of communication in stag hunt coordination games played by members of Senegalese farmer groups—a setting where collective commercialization has suffered from coordination failure, as in many rural contexts. We find that communication increases coordination only in larger experimental groups, where it matters most from the standpoint of poverty traps. We also find that these effects are driven by communication’s impact on perceptions of strategic uncertainty. Some policy implications are discussed.